2015
DOI: 10.1104/pp.114.252841
|View full text |Cite
|
Sign up to set email alerts
|

Small Heat Shock Proteins Can Release Light Dependence of Tobacco Seed during Germination

Abstract: Small heat shock proteins (sHSPs) function as ATP-independent molecular chaperones, and although the production and function of sHSPs have often been described under heat stress, the expression and function of sHSPs in fundamental developmental processes, such as pollen and seed development, have also been confirmed. Seed germination involves the breaking of dormancy and the resumption of embryo growth that accompany global changes in transcription, translation, and metabolism. In many plants, germination is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…Similarly, applications of the plant growth regulator GA 3 or KNO 3 are efficient at releasing Solanum seeds from dormancy and stimulating germination (Hayati et al, 2005;Wei et al, 2010;Gisbert et al, 2011a). Light irradiation, which is an important regulator of seed germination in solanaceous species (Koo et al, 2015), has also been observed to be efficient at stimulating germination in S. torvum seeds. Amazingly, the scarification by NaClO had a highly negative effect on germination.…”
Section: Tablementioning
confidence: 95%
“…Similarly, applications of the plant growth regulator GA 3 or KNO 3 are efficient at releasing Solanum seeds from dormancy and stimulating germination (Hayati et al, 2005;Wei et al, 2010;Gisbert et al, 2011a). Light irradiation, which is an important regulator of seed germination in solanaceous species (Koo et al, 2015), has also been observed to be efficient at stimulating germination in S. torvum seeds. Amazingly, the scarification by NaClO had a highly negative effect on germination.…”
Section: Tablementioning
confidence: 95%
“…The mRNAs from heat shock genes have structures that allow for their selective translation in a stressed cell Mahmood et al 2010). These include a lack of introns, 5 0 -untranslated regions conferring translational efficiency, and 3 0 -untranslated regions providing increased stability (Koo et al 2015). Keeping in view the importance of small heat shock proteins (sHSPs), the present study was designed to identify and compare nine different sHSP gene promoters from rice.…”
Section: Introductionmentioning
confidence: 99%
“…Heat shock proteins (HSPs), also known as molecular chaperones, are known to belong among these stress proteins while they are present in all living organisms (Kim & Hwang 2015). Besides their role in protecting cells against environmental stress conditions, HSPs are essential components of plant cells and they play an important role in protein stabilisation and cellular functions related with plant growth (Pratt et al 2001;Koo et al 2015).…”
mentioning
confidence: 99%
“…In plants, they are classified into five evolutionarily conserved families: HSP100,90,70,60 (or chaperonins), and the small HSPs (sHsps) which have molecular weights of 100, 90, 70, 60, and 12-40 kDa, respectively (AlWhaibi 2011;Koo et al 2015). Higher plants are known to have at least 20 types of sHsps which have an α-crystallin domain consisting of 80-100 amino acid residues in the C-terminal region (Seo et al 2006).…”
mentioning
confidence: 99%